Study the effect of position on the time of astronomical twilight - Fouad M. Abdulla; Anas Salman Taha (مجلة بغداد للعلوم, 2009)
Twilight  is that light appear on the horizon before sunrise and after sunset, Astronomically it is known that sunrise and sunset are effected by high above sea level, but the effect of high above sea level on the time of astronomical twilight still not decided and controversy among astronomers, in This research we studies the effect of high above sea level on the time of astronomical twilight, through adding the equation correct high above sea level to equation computation of twilight and then calculate of changing in the time of twilight for different highest (0-10000) meters above sea level , and the ratio of increase for time with high between (15.45-20.5) minutes. It was found that there was an increase in the time of the twilight along the year when increasing high above sea level and that surely effected time of astronomical twilight with high above sea level, but this effect is strong for high to 2000 meters and then high effect will be less to increasing the time of twilight.